2005
DOI: 10.2465/gkk.34.143
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and Geochemistry of the mantle xenoliths: Implications for lithospheric mantle beneath the Japan arcs

Abstract: Recent developments in instrumentation for in situ trace element analysis of peridotite minerals give us valuable data set of petrological and geochemical insights of the upper mantle. Here, we summarize petrographical, petrological and geochemical characteristics of mantle xenoliths from the Northeastern and Southwestern Japan arcs. They have clear correlations between microtexture and mineral compositions in terms of both major and trace elements. That suggests that influx assisted melt extraction occurs sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In studies carried out on peridotite xenoliths from the Kurose reef, Abe and Arai (2005) suggested that the equilibrium temperature were in the range 900 -1100 °C on the basis of a two -pyroxene geothermometer (Wells, 1977). Since the samples of the present study were obtained from a geological environment similar to that described by Abe and Arai (2005), it is plausible that the lherzolite in the samples of this study crystallized at similar temperatures of 900 -1100 °C.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In studies carried out on peridotite xenoliths from the Kurose reef, Abe and Arai (2005) suggested that the equilibrium temperature were in the range 900 -1100 °C on the basis of a two -pyroxene geothermometer (Wells, 1977). Since the samples of the present study were obtained from a geological environment similar to that described by Abe and Arai (2005), it is plausible that the lherzolite in the samples of this study crystallized at similar temperatures of 900 -1100 °C.…”
Section: Discussionmentioning
confidence: 80%
“…at temperatures >900 °C. On the basis of the equilibrium temperature (900 -1100 °C) of the Kurose mantle xenolith (Abe and Arai, 2005), it can be inferred that the sulfide inclusions of pentlandite were trapped as a sulfide liquid rather than in the solid phase. With decreasing temperature, the solid phase precipitated from the sulfide liquid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We set Ichinomegata and Aratoyama as respective reference points for northeastern and southwestern Japan, and set the equilibrium temperatures to 950 • C and 1050 • C, respectively, using the research result of Arai et al (2007) as a reference. In most cases, the mantle xenoliths obtained in the Japanese Islands were spinel peridotite (Abe and Arai, 2005), which stably exists in the depth range shallower than about 60 km according to a P-T diagram (e.g., Gill, 2010). Therefore, we set the representative depth, at which the mantle xenoliths in the Japanese Islands had existed, to 45 km as the intermediate depth between the Moho boundary (about 30 km) and 60 km.…”
Section: Thermal Structure Below 45 Kmmentioning
confidence: 99%
“…Xenoliths from the mantle wedge Arai and Ishimaru, 2008) have recorded mantle metasomatism (e.g., Arai and Kida, 2000;Abe and Arai, 2005;Ishimaru et al, 2007;Kawamoto et al, 2013). It is well known that ultramafic-mafic xenoliths from Ichinomegata, Northeast Japan arc, contain hydrous minerals (e.g., Kuno, 1967), some of which are of secondary origin (Arai and Saeki, 1980;Takahashi, 1986).…”
Section: Introductionmentioning
confidence: 99%